Financing Mediation on the Effect of Firm Size and Capital Adequatiacy on the Profitability - Desiana, Lidia; Africano, Fernando (Jurnal Aplikasi Manajemen dan Bisnis, 2023)
This research aims to find out how financing mediation Effects firm size and capital adequacy on profitability in Sharia Commercial Banks for the 2016-2020 period. The population is 14 Sharia Commercial Banks with a sample of 7 BUS. The conclusion is that firm size has a negative and significant effect on financing. Meanwhile, Capital Adequacy does not affect Financing. The firm size does not affect profitability. And Capital Adequacy has a positive and significant effect on Profitability. Financing has a positive and significant effect on profitability. Apart from that, Financing can mediate the Effect of Firm size on Profitability, and Financing can mediate the Effect of Capital Adequacy on Profitability.